Function & Application of GIS in Precision Agriculture at Darjeeling Hill - Das, S; Loha, J (International Journal of Computer Sciences and Engineering, 2025)
Being an ancient geographical practice agriculture can be enormously benefited by the application of GIS. For collection of spatially referenced data, to perform spatial analysis, decision making and application of variable rate treatment and specific farming systems may utilize GIS and several related technologies such as global positioning system (GPS), continuous yield sensors, remote sensing (RS) instruments, receivers, etc. These advanced technologies offer numerous advantages to generate & synthesize new information related to agriculture cheaply and quickly; document data source & methods of integration provide diagnostics for error detection and accuracy assessments, prepare maps and tables for proper and various types of cultivation. But due to our lack of knowledge of statistical methods for summarizing spatial patterns, difficulty of moving geographical data and model results between different scales, and cost and difficulty of field validation, we are unable to access the data and maps. This problem can be overcome through the use of GIS and related technologies and this can help us to improve the cultivation or agricultural system in the Darjeeling hills. The main objectives of sustainable agriculture follows: balancing the inherent land resource with crop requirements, optimization of resource use towards achievement of sustained productivity over a long time